OVERVIEW OF GIVING BOILED SOURSOP LEAF WATER TO REDUCE GOUT ARTHRITIS LEVELS IN ELDERLY PATIENTS IN KARANGJAMBU VILLAGE, KARANGJAMBU DISTRICT, PURBALINGGA REGENCY - Fida Dyah Puspasari; Priyatin Sulistyowati; Eko Julianto; Saifuloh, Sofyan (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Gout arthritis is a degenerative disease commonly experienced by the elderly due to elevated uric acid levels in the blood. One safe non-pharmacological treatment alternative is the use of herbal remedies such as soursop leaves (Annona muricata L), which contain active compounds like flavonoids and alkaloids that may reduce uric acid levels. Objective: To describe the effect of boiled soursop leaf water on reducing uric acid levels in elderly patients with gout arthritis in Karangjambu Village, Karangjambu Subdistrict, Purbalingga Regency. Method: This study employed a case study method. Subjects were given an intervention of 200 ml of boiled soursop leaf water daily (100 ml in the morning and 100 ml in the evening) for seven consecutive days. Uric acid levels were measured before and after the intervention. Results: After seven days of soursop leaf water administration, uric acid levels decreased from an average of 8.7–9.0 mg/dl to 5.5–5.8 mg/dl. This suggests that the active compounds in soursop leaves are effective in inhibiting xanthine oxidase and promoting uric acid excretion through urine. Conclusion: Boiled soursop leaf water is effective in lowering uric acid levels in elderly patients with gout arthritis and can serve as a safe and practical complementary non-pharmacological therapy within the community.